Cholesterol and Mevalonate: Two Metabolites Involved in Breast Cancer Progression and Drug Resistance through the ERRα Pathway - Matteo Brindisi; Marco Fiorillo; Luca Frattaruolo; Federica Sotgia; Michael P. Lisanti; Anna Rita Cappello (Cells, 2020)
Breast cancer is the second greatest cause of cancer-related death in women. Resistance to endocrine treatments or chemotherapy is a limiting drawback. In this context, this work aims to evaluate the effects of cholesterol and mevalonate during tumor progression and their contribution in the onset of resistance to clinical treatments in use today. In this study, we demonstrated that cholesterol and mevalonate treatments were able to activate the estrogen-related receptor alpha (ERRα) pathway, increasing the expression levels of peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α), ERbB2/human epithelial receptor (HER2), tumor protein D52 (TPD52), and NOTCH2 proteins in breast cancer cells. The activation of this pathway is shown to be responsible for intense metabolic switching, higher proliferation rates, sustained motility, the propagation of cancer stem-like cells (CSCs), and lipid droplet formation. All of these events are related to greater tumor propagation, aggressiveness, and drug resistance. Furthermore, the activation and expression of proteins induced by the treatment with cholesterol or mevalonate are consistent with those obtained from the MCF-7/TAMr cell line, which is largely used as a breast cancer model of acquired endocrine therapy resistance. Altogether, our data indicate that cholesterol and mevalonate are two metabolites implicated in breast cancer progression, aggressiveness, and drug resistance, through the activation of the ERRα pathway. Our findings enable us to identify the ERRα receptor as a poor prognostic marker in patients with breast carcinoma, suggesting the correlation between cholesterol/mevalonate and ERRα as a new possible target in breast cancer treatment.